2017
DOI: 10.22161/ijeab/2.2.23
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes in leaf-cutting ant Atta sexdens rubropilosa in different developmental stages and tissues

Abstract: Abstract-Atta sexdens rubropilosa is an important leafcutting ant species considered as a pest in agricultural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Two AsChEs were purified from worker heads of A. sexdens . Medium worker ants were selected considering our previous studies, in which we identified higher AChE expression levels in this developmental stage, compared to larva and pupa [40].…”
Section: Resultsmentioning
confidence: 99%
“…Two AsChEs were purified from worker heads of A. sexdens . Medium worker ants were selected considering our previous studies, in which we identified higher AChE expression levels in this developmental stage, compared to larva and pupa [40].…”
Section: Resultsmentioning
confidence: 99%
“…These results do not differ from those found in the reference gene evaluation in A. sexdens rubropilosa , on which RPL18 was the most stable gene in tissues under development stage. [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptide expression levels were determined relative to transcripts of elongation factor‐1 alpha (EF1 α) using the ΔΔCt method. EF1 α was shown to be a suitable reference gene in brains of honeybees (Lourenço et al, 2008; Reim et al, 2013) and several ant species (Moreira et al, 2017; Ratzka et al, 2011). Therefore, we decided to use this gene in C .…”
Section: Methodsmentioning
confidence: 99%